Tiger-Hunting' and Life Satisfaction: A Matter of Trust - Youxing Zhang; Peter Howley; Clemens Hetschko (Center for Economic Studies and ifo Institute (CESifo), 2022)
Governments will often look to publicly signal their efforts to tackle issues of concern as a way of garnering political support. Combining data on the public disclosure of anti-corruption efforts and individual well-being in China, we show that such signals may increase the salience of the issue in question and hence diminish the life satisfaction of citizens with low political trust. For citizens with high trust, such signals appear to enhance life satisfaction. This means that signalling efforts may have unintended negative consequences on population well-being and thus political support, particularly when faced with low political trust.
Keywords: D73; I31; P48; O17; 330; corruption; life satisfaction; political trust; signalling theory; confirmation bias